Comparison of artificial and natural, new and reused, brackish water for the larviculture of the freshwater prawn Macrobrachium rosenbergii in a recirculating system - Mallasen, Margarete [UNESP]; Valenti, Wagner Cotroni [UNESP] (Wiley, 1998)
Differences in culture duration, metamorphosis rate and the productivity in hatchery culture of M. rosenbergii using a closed system with natural and artificial brackish water were evaluated. Reuse of brackish water in more than one hatchery cycle was also evaluated. Natural and artificial brackish water constituted the two tested treatments, which were distributed in four independent recirculating systems (tank and respective biofilter). Four batches of cultures were conducted and the 2nd and 4th reused the water from the 1st and 3rd, respectively. Mean duration of the hatchery period was 28 d in natural brackish water and 31 d in artificial brackish water. The metamorphosis rate and the average productivity for the natural brackish water treatment were 74% and 60 postlarvae/ L. respectively, and values obtained with artificial brackish water were 55% and 44 postlarvae/L. The successful hatchery culture of M. rosenbergii in this specific artificial brackish water suggests its potential use in enterprises located far from the coast. Brackish water can be used in two consecutive cultures without a negative effect on productivity.
Keywords: aquaculture system; brackish water; hatchery; larval development; Macrobrachium rosenbergii